Structural Investigation and Properties Of Tio2 Thin Film Prepared by Sol-Gel Spin Coating - Diani Galih Saputri; Mohd Khairul Bin Ahmad; Agus Supriyanto; Achmad Nasyori; Salisu I Kunya; Nurul Amiera Shahida Maarof; Siti Nurhaziqah Abd Majid; Anis Zafirah Mohd Ismail; Shazleen Ahmad Ramli (Department of Physics, Sebelas Maret University, 2022)
We report the structural properties of TiO2 (Titanium dioxide) thin films grown using sol-gel spin coating method for temperature treatment (with temperature 50o C and without temperature) The difference in temperature is carried out to determine changes in the surface of the sample by using heating or not. Ideally, the thickness of the TiO2 layer ranges from 10-15 μm, therefore in this study it was carried out in 5 layers. Field Emission Scanning Electron Microscopy (FESEM) consist of surface morphology, Cross-section sample, and EDX images, respectively, providing the structure of the surface. The result confirm that temperature treatment can damage the surface coating, this is proven by the shape of the crack in the coating.